2021
DOI: 10.1002/aah.10128
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic Efficacy of Crude Plant Extracts and Compounds Purified from Plants against the Fish Monogenean Neobenedenia girellae

Abstract: Neobenedenia girellae is a pathogenic ectoparasite of many marine fishes, and it causes major epidemics in marine aquaculture. In this study, the efficacy of ethanol extracts of huangqi Astragalus membranaceus (known as milkvetch in North America), guanzhong Dryopteris setosa (known as beaded wood fern in North America), gancao Glycyrrhiza uralensis (known as Chinese licorice in North America), danshen Salvia miltiorrhiza (known as red sage in North America), and pomegranate Punica granatum, as well as seven p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Among the different phytogenic compounds tested, curcumin and cedrol presented the lowest LC 50 values, garlicin and eucalyptol showed intermediate effects, while r-camphor was the least effective. Nevertheless, another in vitro study demonstrated that curcumin was not effective against the parasite Neobenedenia girellae [ 65 ]. These studies revealed that the use of compounds derived from Allium , to a greater or lesser extent, is effective for the control of gill parasites, although their degree of efficacy will depend, among other factors, on the species of the target parasite, the composition of the active ingredients and the dose of inclusion in the feed.…”
Section: Discussionmentioning
confidence: 99%
“…Among the different phytogenic compounds tested, curcumin and cedrol presented the lowest LC 50 values, garlicin and eucalyptol showed intermediate effects, while r-camphor was the least effective. Nevertheless, another in vitro study demonstrated that curcumin was not effective against the parasite Neobenedenia girellae [ 65 ]. These studies revealed that the use of compounds derived from Allium , to a greater or lesser extent, is effective for the control of gill parasites, although their degree of efficacy will depend, among other factors, on the species of the target parasite, the composition of the active ingredients and the dose of inclusion in the feed.…”
Section: Discussionmentioning
confidence: 99%